Development of a practitioner training model: a metacognitive approach based on the Denver II developmental screening test - Kuralbayeva, Aliya; Pilten, Gülhiz; Tasova, Asel; Pilten, Pusat (Frontiers in Education, 2025)
IntroductionThis study introduces a training model developed to support practitioners in effectively using the Denver II Developmental Screening Test. The model was shaped through a five-step process and is grounded in metacognitive principles. It aims to help practitioners not only follow steps but also pause, anticipate challenges, and consider their actions—practices often neglected in typical training.MethodsThe model development process involved qualitative data collection with fifteen early childhood professionals who engaged with the model during its implementation. Their feedback and observed behaviors were qualitatively examined. Additionally, insights were obtained from several field experts who reviewed the model.ResultsFindings indicated that the model was perceived as flexible and relevant across diverse practice settings. Experts highlighted its applicability in improving practitioners’ ability to reflect, self-monitor, and adapt their professional judgment during the use of developmental screening tools.DiscussionThe model’s contribution lies in shifting the focus from simply following procedures to fostering practitioners’ cognitive and metacognitive engagement in decision-making. While developed around the Denver II framework, the approach shows potential to inform practices in related assessment contexts.